HUMAN RESOURCE MANAGEMENT IN THE CONDITIONS OF MARTIAL STATE: INTEGRATION OF DIGITAL TECHNOLOGIES - ZAMLYNSKYI, Viktor; SKRYPNYK, Nataliia; FEDAKA, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the essence and trends of personnel management in martial law and summarizes the advantages and disadvantages of implementing digital technologies in the HR management system. The purpose of the study is to substantiate the effectiveness of digital personnel management tools to increase the resilience of enterprises during crisis risks. The need for personnel adaptation to operations in wartime, the development of motivational measures to retain professional personnel and prevent their outflow are analyzed. Key competencies that ensure personnel development and affect the efficiency of the enterprise’s functioning in crisis conditions are identified. The main problems that enterprises face in personnel issues due to military operations are considered, in particular the impact on the quality of management and the use of socio-psychological methods of remote management. Key trends in HRM are identified, such as the emphasis on employee retention, the implementation of lifelong learning programs, retraining, supporting employee health, and the development of organizational culture. The problems of staffing, adaptation, and retention of personnel in martial law are summarized. The integration of innovative digital technologies into HR practice can slow down the processes of losing the best employees and invest in retaining existing employees, because rapid technological development requires constant training and skill development. Rapid technological development optimizes the interdependence between successful human resource management and improving the efficiency of the enterprise, therefore requiring the adaptation of HR management strategies focused on flexibility, efficiency and stimulating innovation. The implementation of digital HRM tools contributes to the optimization of processes, but requires solving the challenges associated with staff retraining and adaptation to new conditions. The article concludes on the importance of optimizing HR management strategies to increase the sustainability and competitiveness of enterprises in the face of modern challenges of Ukrainian business.